Biofuel Investments in Sub-Saharan Africa: A Review of the Early Legal and Institutional Framework in Zambia - German, L.; Schoneveld, George C. (Wiley, 2012)
Concerns about domestic energy security and global climate change mitigation have led the European Union, the United States, and others to introduce policies to enhance the use of biofuels in the transport sector fuel mix. While countries throughout the global South are positioning themselves to capture the economic benefits of this fuel transition, their capacity to do so is highly variable. This paper reviews the early evolution of the biofuel sector in Zambia to explore the extent to which the country is positioned to leverage future benefits of the emerging industry while forestalling negative social and environmental costs. In doing so, it sheds light on an under‐researched dimension of the ongoing debate over large‐scale land acquisitions and foreign investment: the role of legal and institutional frameworks in host countries in shaping outcomes. The analysis draws on the following: policy documents; stakeholder interviews with government departments, investors, and civil society stakeholders; and published and reported data on investments. Findings suggest that while existing and incipient policies and legislation provide an important foundation for attracting investors and achieving diverse sector aims, a number of gaps remain that are likely to hinder efforts to leverage meaningful benefits while minimizing negative impacts.